2016
DOI: 10.1038/ejcn.2016.166
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term treatment of phenylketonuria with a new medical food containing large neutral amino acids

Abstract: Background/Objectives:Phenylketonuria (PKU) is an autosomal recessive disease caused by deficient activity of phenylalanine hydroxylase. A low phenylalanine (Phe) diet is used to treat PKU. The diet is very restrictive, and dietary adherence tends to decrease as patients get older. Methods to improve dietary adherence and blood Phe control are continuously under investigation.Subjects/Methods:A new formula Phe-neutral amino acid (PheLNAA) has been tested in this study with the purpose of improving the complian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…However, clinical measures of downstream LNAA metabolites (ie, respective keto‐acids, histamine from histidine, cysteine from methionine) in patients with PKU, combined with dietary intake and plasma concentrations, are needed to identify the mechanisms that maintain stable LNAA plasma levels relevant to diet patterns . Additionally, measuring flux across membrane barriers for cellular uptake could add further insight, particularly as studies have shown that prescribing LNAA supplements to patients with PKU may be an effective therapy due to competitive inhibition of PHE across both the gut and blood brain barriers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, clinical measures of downstream LNAA metabolites (ie, respective keto‐acids, histamine from histidine, cysteine from methionine) in patients with PKU, combined with dietary intake and plasma concentrations, are needed to identify the mechanisms that maintain stable LNAA plasma levels relevant to diet patterns . Additionally, measuring flux across membrane barriers for cellular uptake could add further insight, particularly as studies have shown that prescribing LNAA supplements to patients with PKU may be an effective therapy due to competitive inhibition of PHE across both the gut and blood brain barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma P:T ratio, residuals 3 Table 2). When evaluating the full cohort with Kendall's tau, P:T ratio had significant inverse correlations with all plasma LNAA concentrations (P ≤ .028) except for isoleucine (τ = −0.166, P = .056).…”
Section: Lnaa Interaction With Plasma Phe Tyr and P:t Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…Hoeksma et al [ 22 ] demonstrated a significant negative correlation between plasma Phe concentration and cerebral protein synthesis in patients with PKU. This leads to development of new medical foods with higher concentrations of LNAA and fortification with vitamins and lutein, an antioxidant important for the development of the brain [ 23 ]. Studies in PAH enu2 mice provide support for the use of a variety of non-physiological amino acids to act as competitive inhibitors of brain transporters to reduce brain Phe concentrations with minimal impact on other down-stream intermediates [ 24 ].…”
Section: Large Neutral Amino Acid Supplementationmentioning
confidence: 99%
“…A new medical food Phe LNAA fortified with Vitamin B 12 , biotin, docosahexaenoic acid (DHA), and lutein have been developed for the long‐term treatment of PKU (Concolino et al, ). Goda and Group () synthesized a modified gene sequence of bovine α‐casein replacing all the Phe with Tyr and expressed in E. coli for PKU patients.…”
Section: Introductionmentioning
confidence: 99%